Advances in Human Factors in Energy: Oil, Gas, Nuclear and Electric Power Industries Proceedings of the AHFE 2016 International Conference on Human Factors in Energy: Oil, Gas, Nuclear and Electric Power Industries, July 27-31, 2016, Walt Disney World®, Florida, USA - Cetiner, Sacit M.; Fechtelkotter, Paul.; Legatt, Michael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book addresses human factors research in energy, an emphasis on human factors applications in design, construction, and operation of nuclear, electrical power generation, and oil and gas assets. It discusses advanced strategies in the optimization of human and environmental performance, as well as personal and process safety. The book covers a wealth of topics in design and operation management of both offshore and onshore facilities, including design of control rooms, front-end engineering design (FEED), criticality analysis, offshore transport, human contributions to accidents, cognitive bias in decision making, safety-critical human tasks, and many others. Based on the AHFE 2016 International Conference on Human Factors in Energy, held on July 27-31, 2016, in Walt Disney World®, Florida, USA, the book fills an important gap in the current literature, providing readers with state-of-the-art knowledge in human factors best-practice approaches across different types of industries and energy applications.
Reducing Human Error Through Situation Awareness, Training, and Simulations -- Applying Human Factors: Building Better Processes, Procedures and Organizations in Energy -- Human Factors in Energy -- Simulation and Interface Design for Safety Focused Research.
Keywords: Computational intelligence; Energy policy; Energy and state; Mineralogy; Offshore structures; Computational Intelligence; Energy Policy, Economics and Management; Mineralogy; Offshore Engineering